AMPLATZER™ Duct Occluder II AS embolization to left pulmonary artery related to thrombolytic therapy: Surgical rescue without cardiopulmonary bypass. (March 2019) - Éden Santos, P.; Correia-Costa, A.; Pissarra, Diana; Moreira, J.; Carlos Silva, J.; Rodrigues Sousa, A.; João Baptista, M.
Abstract: We report a case of a 7-month-old girl (5.2 kg), submitted to transcatheter closure of patent ductus arteriosus with AMPLATZER™ Duct Occluder II AS device. Six hours after the procedure the patient developed right inferior limb coldness with absent pedal and tibial pulse. Unfractionated heparin was immediately started. Doppler ultrasound confirmed the absence of flow in the right femoral artery, and thrombolysis with Alteplase infusion began, with positive results in the inferior limb ischemia. The next morning echocardiogram showed a newly-patent ductus arteriosus . CT-angiography revealed an embolized device into the inferior lobar left pulmonary artery. Thus, to prevent late effects of a foreign object in the pulmonary artery, the patient was referred to surgery for device retrieval. Surgery outcome was positive without cardiopulmonary bypass. There was no sign of thrombus formation in the device mesh. Recovery was uneventful, and the patient was discharged five days after the operation. To our knowledge, this is the first patient in whom surgery rescue of this specific device was successfully performed without the need of cardiopulmonary bypass. Highlights: The ADO™ II AS is a PDA device occluder which allows a safe and efficient implantation in neonates and small infants. Reports of this device's embolization are rare. In this case, the embolization may be related to thrombolytic therapy (unusual). Most of the surgical attempts to remove these devices were conducted with the aid of cardiopulmonary bypass. In this case, surgery outcome was positive without cardiopulmonary bypass avoiding the endeavour and risks related to it.